First-principles study of the enhancement of electrochemical performance of a SnS2 monolayer for lithium/sodium-ion batteries via vacancy defects - Mapasha, Refilwe Edwin (University of Pretoria, 2023)
Dissertation (MSc (Physics))--University of Pretoria, 2023.